Beyond Human, Beyond Words: Anthropocentrism, Critical Pedagogy, and the Poststructuralist Turn - Bell, Anne; Russell, Constance (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
Critical pedagogy, even as inflected by certain poststructuralisms, tends to reinforce rather than subvert deep-seated humanist assumptions about humans and nature by taking for granted the borders that define nature as the devalued Other. These assumptions are called into question by discussion of how relationships between language, communication, and meaningful experience are conceptualized outside the field of critical pedagogy. We deal constructively with some anthropocentric blind spots within critical pedagogy generally and within poststructuralist ap- proaches to critical pedagogy in particular. We hope to illuminate places where these streams of thought and practice move in directions compatible with critical environmental education. La pédagogie critique, même celle de quelques poststructuralismes, a tendance à renforcer plutôt que de mettre en doute certains postulats humanistes selon lesquels la nature est, pour les êtres humains, l’Autre dévalué. Ces postulats sont remis en question dans les analyses portant sur le mode de conceptualisation, en dehors du champ de la pédagogie critique, des relations entre le langage, la communication et l’expérience signifiante. Les auteures traitent de quelques présupposés anthro- pocentriques de la pédagogie critique, en particulier dans ses approches post- structuralistes. Elles espèrent ainsi éclairer des courants théoriques et pratiques compatibles entre la pédagogie critique et le respect de l’environnement.